Analysis of porewater and bottom water dissolved organic matter of hydrothermal sediments in the Guaymas Basin - Brünjes, Jonas; Schubotz, Florence; Teske, Andreas P; Seidel, Michael (PANGAEA, 2025)
Analysis of porewater and bottom water dissolved organic matter (DOM) of hydrothermal sediments (3 to 106 C) in the Guaymas Basin. Samples were taken by HOV Alvin during cruise Atlantis AT 42-05 in November 2018. Dataset contains quantitative and qualitative analysis of bulk water and solid-phase extracted (SPE) DOM. We determined DOC and TDN concentrations of bulk water and SPE-DOM along with absorbance and fluorescence measurements. Fluorescence of excitation-emission matrices (EEMs) was decomposed by parallel factor analysis (PARAFAC) and resolved in 7 components. SPE-DOM was analyzed on the molecular level by ultrahigh-resolution mass spectrometry (FT-ICR-MS) and individual molecular formulae were assigned.
Keywords: deep sea sediment; Dissolved Organic Matter; FT-ICR-MS; hydrothermal activity; Oil seeps; PARAFAC; porewater; sulfurization